The Art Of Exiting A Peg: The Case Of Malaysia - Nursilah Ahmad; Asma Abdul Rahman (USIM Tijarah Holding Sdn. Bhd., 2024)
. The switching of exchange rate regimes may have a significant impact on the macroeconomic fundamentals of the economy. The study evaluates Malaysia’s macroeconomic fundamentals to determine whether Malaysia has exited the pegged regime in an orderly manner during the 1997 Asian financial crisis. Based on visual impressions and the analysis of selected macroeconomic fundamentals for the period 1998 to 2005, Malaysia fits the general pattern of an orderly exit with a gradual pace. The next challenge for Malaysia is to maintain a credible regime that is consistent with the underlying economic fundamentals and sustain post-exit growth performance, especially during currency crises. Exchange rate flexibility is still an important determinant in the growth of international financial markets, especially for emerging market economies.